2013
DOI: 10.1590/s0080-623420130000500017
|View full text |Cite
|
Sign up to set email alerts
|

Burden in family caregivers of the elderly: prevalence and association with characteristics of the elderly and the caregivers

Abstract: A cross-sectional, epidemiological study aimed to estimate the prevalence of burden among family caregivers of impaired elderly residents in the city of João Pessoa, and to identify associations between the mean burden and social and demographic characteristics of the elderly and the caregivers. A total number of 240 elderly residents in a previously drawn census tract participated in this research. The sample was composed of 52 elderly and their caregivers. For data collection, a questionnaire was applied wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 15 publications
4
20
2
3
Order By: Relevance
“…Dois estudos realizados com amostras numerosas de cuidadores residentes no Paraná revelaram a prevalência de sobrecarga moderada a severa em mais de 70% dos familiares responsáveis pelo cuidado de idosos dependentes 7,8 . Em São Paulo e na Paraíba, Yamashita et al 9 e Loureiro et al 10 também identificaram a ocorrência de estresse em 69% e 84% dos cuidadores, respectivamente. Comparados com os achados desses estudos, os níveis de sobrecarga inferiores a 30% podem ser considerados reduzidos nos cuidadores examinados em São Paulo por Gratão et al 6 , numa pesquisa cuja prevalência de dependência foi de apenas 15%.…”
Section: Introductionunclassified
“…Dois estudos realizados com amostras numerosas de cuidadores residentes no Paraná revelaram a prevalência de sobrecarga moderada a severa em mais de 70% dos familiares responsáveis pelo cuidado de idosos dependentes 7,8 . Em São Paulo e na Paraíba, Yamashita et al 9 e Loureiro et al 10 também identificaram a ocorrência de estresse em 69% e 84% dos cuidadores, respectivamente. Comparados com os achados desses estudos, os níveis de sobrecarga inferiores a 30% podem ser considerados reduzidos nos cuidadores examinados em São Paulo por Gratão et al 6 , numa pesquisa cuja prevalência de dependência foi de apenas 15%.…”
Section: Introductionunclassified
“…8 The total average burden of family caregivers in this study was similar to other studies that had the purpose of evaluating this phenomenon among caregivers. 9 Some studies have shown that caregivers with a high degree of overload are more easily affected by diseases such as depression, with an average frequency of 30% of observed caregivers. 10 Family members who take on the role of caregivers can get into a crisis situation, and may feel tension, stress, frustration, fatigue, embarrassment, depression and impaired self-esteem, resulting in physical, psychological, emotional, social and financial problems, which in turn affect the well-being of the patient and the caregiver.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to personal income (Table 4), those with higher incomes had higher scores in the areas 'mental health' (64.63) and 'vitality' (76.51). Caregivers with more advanced age are more prone to the negative impact of care, due to increased vulnerability to illness from senescence (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) , as well as the fact that it is women who usually accumulate various roles throughout life, both in society and in caring for the children, the spouse, and the household chores.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the provision of care takes place in conditions of scarcity, and the situation is seen by the caregiver as a duty and they have no alternative option. Therefore, this activity causes stress and feeling of anxiety among caregivers seeking to provide the best care for the family dependent (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation